Menginvestigasi Penyebab Kecanduan Media Sosial pada Mahasiswa Politeknik Negeri Malang - Narasuci, Win; Unarto, Tirto; Budiarti, Lina; Wijayanti, Rena Fery (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the factors that may influence social media addiction among students at the State Polytechnic of Malang. The research was conducted over a three-month period, from June to August 2025, using a quantitative approach. The sample consisted of 161 respondents, all of whom were students majoring in Marketing Management at the State Polytechnic of Malang. The data were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS 3 software. This method was chosen due to its ability to handle complex relationships between latent variables and to provide more accurate and reliable results. The findings of the study reveal that narcissism and emotional problems have a significant positive effect on self-esteem. In addition, self-esteem is found to significantly influence social media addiction, indicating that individuals with lower self-esteem are more likely to develop addictive behaviors toward social media platforms. Moreover, the study also found that narcissism and emotional problems indirectly affect social media addiction through self-esteem as a mediating variable. These results suggest that self-esteem plays a crucial mediating role in the relationship between psychological traits and social media addiction. Therefore, efforts to address social media addiction among students should also consider psychological factors such as self-esteem, narcissism, and emotional well-being.